Is ERM a Reputational Asset or Liability? Evidence from Operational Risk Announcements in Financial Institutions - Kabir, Bushra (2017)
Ideally, the board and the management can be envisioned as two intertwined ropes that hold a company together. This study endeavours to evaluate whether risk management translates as a reputational asset or liability for a financial institution. To do so, it accounts for the collective impact of ERM (considering both the board and the management function of a firm) on reputational losses arising out of operational risk events. It involves an event-study regression analysis of 352 operational loss announcements from 110 financial firms in 26 countries for post-crisis years 2010-2014. The findings from the correlation analysis reveal significant negative association between reputational losses and CEO-Chairman duality, board independence, AC size and RMC size. The regression analysis reveals a negative and close to significant relationship between reputational losses and RMC size, but further renders the marginal impact of board characteristics and CRO characteristics to be negative but not significant. In that sense, ERM can be interpreted as a reputational liability. The findings gain support from the Expectation Violation Theory and Perry and Fontnouvelle’s (2005) ‘smoking gun’ effect. That reputational losses occur despite pre-existing control measures highlights that investors are sensitive to losses arising out of operational neglect. This causes them to lose prior optimistic faith in firm management, and hence reputational losses are incurred. Most importantly, the findings underline that mere existence of ERM measures does not shield a firm against reputational loss arising out of operational risk.